2014
DOI: 10.1002/ejic.201301598
|View full text |Cite
|
Sign up to set email alerts
|

A Catalyst with Two‐Coordinate Nickel: Theoretical and Catalytic Studies

Abstract: The bisadduct (cAAC)2NiIICl2 [1; cAAC = cyclic (alkyl)(amino)carbene] was directly synthesized by treating cAAC with NiCl2. Compound 1 was reduced to (cAAC)2Ni0 (2) by using lithium diisopropylamide or KC8. Crystals of 2 were stable under an inert gas for several months and decomposed upon heating above 165 °C. On the basis of the calculated natural bond orbital charge values of the nickel atom in 2, the oxidation state of nickel was determined to be between NiI and Ni0 (+0.34). Theoretical calculations sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 48 publications
4
64
0
Order By: Relevance
“…The molecular structure of 8 was determined by single‐crystal X‐ray diffraction (Figure ) and reveals the expected tetrahedral geometry around the metal atom, with bond angles between 107 and 111°. The Ni1−C1 distance to the carbene carbon atom of 1.9629(13) Å in 8 is significantly (0.114 Å) longer than the Ni−C CAAC bond length of 1.849(4) Å observed for the more electron‐rich, two‐coordinate complex [Ni(CAAC methyl ) 2 ] ( 9 ) . It is, however, in good agreement with those of other NHC‐containing nickel tricarbonyl complexes, such as [Ni(CO) 3 (SIPr)] (1.962(4) Å) and [Ni(CO) 3 (SIMes)] (1.960(2) Å) .…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The molecular structure of 8 was determined by single‐crystal X‐ray diffraction (Figure ) and reveals the expected tetrahedral geometry around the metal atom, with bond angles between 107 and 111°. The Ni1−C1 distance to the carbene carbon atom of 1.9629(13) Å in 8 is significantly (0.114 Å) longer than the Ni−C CAAC bond length of 1.849(4) Å observed for the more electron‐rich, two‐coordinate complex [Ni(CAAC methyl ) 2 ] ( 9 ) . It is, however, in good agreement with those of other NHC‐containing nickel tricarbonyl complexes, such as [Ni(CO) 3 (SIPr)] (1.962(4) Å) and [Ni(CO) 3 (SIMes)] (1.960(2) Å) .…”
Section: Resultssupporting
confidence: 58%
“…Interestingly, [Ni(CO) 3 (CAAC methyl )] ( 8 ) can also be synthesized by the reaction of [Ni(CAAC methyl ) 2 ] ( 9 ) with an excess of CO with concomitant carbonylation of the released carbene ligand. Treatment of the mono‐CAAC‐ligated complex 8 with additional carbene 1 , however, resulted in the substitution of two carbonyl ligands and the formation of [Ni(CO)(CAAC methyl ) 2 ] ( 10 ), the formal product of coordination of carbon monoxide to bis‐carbene complex 9 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…However, Wolters and Bickelhaupt found that π‐back‐donation can stabilize smaller angles in d 10 [ML 2 ] complexes . We note that there is experimental evidence for this statement, as the complex [Ni(CAAC) 2 ] (CAAC=cyclic alkyl(amino)carbene), bearing a much stronger π* acceptor than NHC ligands, exhibits a bent structure in contrast to its linear NHC analogues (Table S3 in the Supporting Information) . The H 2 Im ligand in anionic Group 9 complexes acts as a strong π* acceptor, and thus allows the formation of bent d 10 [M(H 2 Im) 2 ] complexes and distorted tetrahedral d 10 [M(H 2 Im) 4 ] structures (see Table S1 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 86%
“…There are strong π back‐donations from metal to carbene carbon atoms which might be a possible reason (M=Fe, Co, Ni, Pd, Pt). Note, that there is no radical electron on the carbene carbon atom for M=Fe, Co, Ni,12bd Pd, Pt. The orientation of two cAACs in (cAAC) 2 M has huge effect on the spin ground state and fine electronic structure.…”
Section: Methodsmentioning
confidence: 99%